Disulfide bridge formation to increase thermostability of DFPase enzyme: A computational study. (December 2018) - Mohammadi, Mozafar; Sakhteman, Amirhossein; Ahrari, Sajjad; Hassanpour, Kazem; Hashemi, Sayed Ebrahim; Farnoosh, Gholamreza
Graphical abstract: Highlights: The most important problem with the bio-catalytic enzymes such as DFPase is their instability against the high temperatures. Introducing the disulfide bridges is one of the most common approaches to improve protein thermostability. We applied insilico approaches to design the disulfide bridge and evaluate its role in the DFPase enzyme thermostability. According to the in silico results, mutants 6 (V24C, C76) increased the enzyme thermostability. Abstract: Organophosphate compounds bioremediation by use of organophosphorus degradation enzymes such as DFPase is a developing interest in industry and medicine. The most important problem with the bio-catalytic enzymes is their instability on high temperatures. This work carried out to find suitable locations for introducing disulfide bridges in DFPase enzyme. We employed some computational approaches to design the disulfide bridges and evaluate their roles in the enzyme structural thermostability. According to the in silico results, mutant 6 (V24C, C76) increased the enzyme thermostability relative to wild-type.